STRUKTUR GENETIK POPULASI IKAN CAKALANG, Katsuwonus pelamis (Linneaus, 1758) DI PERAIRAN LAUT MALUKU UTARA, INDONESIA - Akbar, Nebuchadnezzar; Labenua, Rusmawati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Genetic is key substantial approach conservation, managament and sustainability. This study aims to genetic structure populations Skipjack tuna in North Maluku Sea. Samples collection in Morotai Island (n=10), Central Halmahera District, Weda (n=10) dan South Halmahera District, Bacan, (n=10) and secondary data (n=4) in March-May 2018. Molecular analysis through stages extraction, PCR, electrophoresis and sequencing DNA. DNA sequences analysis used MEGA 5 (Genetic distance and phylogenetic) and arlequin (Fixation index). The result found that fragment length 546 (base pairs) in control mitocondrial DNA. Genetic distance analysis Skipjact tuna population based on primary (North Maluku) and secondary data (Sulu-Celebes and South China Sea, Bali, Indian coast, Kyushu Island Japan) show close genetic 0.037-0.056. Fixation indices (Fst) analysis value 0.801-0.936 the show that weak genetic differentiation between populations. High genetic flow between populations based on genetic distance and Fst. The result show that genetic distance and Fst show that genetic structure populations Skipjack tuna in North Maluku Sea undistrubed. The Skipjack tuna data obtained can uses data base to preserve and sustainability fish resource.